The effect of recombinant human soluble thrombomodulin on renal function and mortality in septic disseminated intravascular coagulation patients with acute kidney injury: a retrospective study - Masayuki Akatsuka; Yoshiki Masuda; Hiroomi Tatsumi; Tomoko Sonoda (Journal of Intensive Care, 2020)
Abstract Background Clinical evidence showing the effectiveness of recombinant human soluble thrombomodulin (rhTM) for treating sepsis-induced disseminated intravascular coagulation (DIC) and organ dysfunction (particularly renal injury) is limited because of differences in the inclusion criteria and disease severity among patients. This study aimed to assess the association between rhTM and outcomes in septic DIC patients with acute kidney injury (AKI). Methods This retrospective observational study analyzed the data of patients who were admitted to the intensive care unit (ICU) of a single center between January 2012 and December 2018, and diagnosed with sepsis-induced DIC and AKI. Data were extracted as follows: patients’ characteristics; DIC score, as calculated by the Japanese Association for Acute Medicine and the International Society of Thrombosis and Hemostasis criteria; serum creatinine levels; and ICU and 28-day mortality rates. The primary outcome was the dependence on renal replacement therapy (RRT) at ICU discharge. The propensity score (PS) was calculated using the following variables: age, sex, septic shock at admission, DIC score, and KDIGO classification. Subsequently, logistic regression analysis was performed using the PS to evaluate the outcome. Results In total, 97 patients were included in this study. Of these, 52 (53.6%) patients had received rhTM. The dependence on RRT at ICU discharge was significantly lower in the rhTM than in the non-rhTM group (odds ratio [OR], 0.43; 95% confidence interval [CI], 0.19–0.97; P = 0.043). The serum creatinine levels at ICU discharge (OR, 0.31; 95% CI, 0.13–0.72; P = 0.007) and hospital discharge (OR, 0.25; 95% CI, 0.11–0.60; P = 0.002, respectively), and the 28-day mortality rate (OR, 0.40; 95% CI, 0.17–0.93; P = 0.033) were significantly lower in the rhTM than in the non-rhTM group. Moreover, the Kaplan–Meier survival curve revealed significantly lower mortality rates in the rhTM than in the non-rhTM group (P = 0.009). No significant differences in the DIC score and AKI severity were observed between the groups. Conclusions Among sepsis-induced DIC patients with AKI, rhTM administration was associated with lower dependence on RRT at ICU discharge, improvement in renal function, and lower 28-day mortality rate.